The politics of Middle English parables : fiction, theology, and social practice - Raschko, Mary (Manchester medieval literature and culture, 2019)
The politics of Middle English parables examines the dynamic intersection of fiction, theology and social practice in late-medieval England. Parables occupy a prominent place in Middle English literature, appearing in dream visions and story collections as well as in lives of Christ and devotional treatises. While most scholarship approaches the translated stories as stable vehicles of Christian teaching, this book highlights the many variations and points of conflict across Middle English renditions of the same story. In parables related to labour, social inequality, charity and penance, the book locates a creative theological discourse through which writers attempted to re-construct Christian belief and practice. Analysis of these diverse retellings reveals not what a given parable meant in a definitive sense but rather how Middle English parables inscribe the ideologies, power structures and cultural debates of late-medieval Christianity.